Altitude Aerosol Measurements in Central France: Seasonality, Sources and Free‐Troposphere/Boundary Layer Segregation. Issue 3 (18th March 2021) - Farah, A.; Freney, E.; Canonaco, F.; Prévôt, A. S. H.; Pichon, J‐M.; Abboud, M.; Farah, W.; Sellegri, K.
Abstract: The chemical composition of nonrefractory submicron aerosol particles was measured at the Puy‐de‐Dôme (PUY) station (1, 465 m a.s.l) during 2015 using a Time‐of‐Flight Aerosol Chemical Speciation Monitor (ToF‐ACSM). These aerosol chemistry measurements are combined with online black carbon (BC) measurements to provide an overview of the submicron aerosol composition. Averaged over the entire year, and normalized to standard temperature and pressure, organic aerosol (OA) dominates the PM1 concentration during all seasons and within all air mass types (2.12 ± 1.73 µgm −3 ), and is responsible for summertime increases in aerosol concentration. Highest mass concentrations were measured during the summer, when air masses were arriving over mainland Europe and lowest in the winter months (when most air masses were of Atlantic origin). OA source apportionment was performed separately during each season, using the Source Finder (SoFi) interface for the multilinear engine. The PUY site, situated at 1, 465 m a.s.l, although mainly sampling in the atmospheric boundary layer, it is sometimes sampling in the lower free troposphere (FT), providing the opportunity to identify the characteristics of FT aerosol. In order to accurately identify these sampling periods, the methodology described in Farah et al. (2018), during the same time period (2015/2016), was applied to the data. During this period, FT air masses are sampled approximately 20% of the time. This work provides, on one hand, a description of long‐term aerosol chemical properties at a remote regional site in central Europe and, on the other hand a characteristic chemical signature of FT aerosols over this region. This data can be used to improve our understanding of the transport and aging properties of aerosols at regional observation sites. Key Points: Statistical analysis of one year of aerosol chemical data at the Puy‐de‐Dome research station Evidence of biomass burning injections into free troposphere (FT) during spring seasons Chemical signature of FT aerosol particles identified